CONFORMATIONAL STUDIES OF LIGNANS FROM Durio oxleyanus Griff. (Bombacaceae) - Rudiyansyah Rudiyansyah; Lynette K Lambert; Mary J Garson (Universitas Gadjah Mada, 2010)
Searching for secondary metabolites from the wood bark of Durio oxleyanus has afforded two new lignans, namely threo-carolignan Y (1) and erythro-carolignan Y (2) together with three other known lignans erythro-carolignan X (3), boehmenan X (4) and boehmenan (5). The relative configurations of compounds 1 and 2 were established by J-based configurational analysis and 2D NOESY studies.